UNRAVELING THE CHALLENGES OF INDONESIAN NOVICE TEACHERS OF ENGLISH - Widiati, Utami; Suryati, Nunung; Hayati, Nur (Indonesian Journal of Applied Linguistics, 2018)
This paper reports on a study aiming to unravel the challenges that Indonesian novice teachers of English have to cope with, in terms of lesson planning and implementation, classroom management, and professional development. It also inquires into the teachers’ pre-service teacher education experience and support system provided by the school, which might relate to their challenges. The study is a qualitative case study involving eleven English teachers of secondary schools (junior and senior high schools and vocational schools) in Malang areas who have less than five years of teaching experience. Data were collected through open-ended questionnaires followed up with semi-structured interviews as a means to clarify and elaborate what the respondents had written in the questionnaires. The study reveals various challenges faced by these novice teachers, including planning and implementing a lesson based on the 2013 Curriculum, designing and applying motivating learning strategies and assessment procedure that would be applicable to a class of students with a relatively low level of ability, and managing a big class. It concludes with some recommendations to bridge the gap between the pre-service and in-service teacher education and professional development.